Liquid crystalline bilayers self-assembled from rod–coil diblock copolymers. Issue 26 (12th June 2017) - Cai, Yongqiang; Zhang, Pingwen; Shi, An-Chang
Abstract : In this paper, we study the occurrence and stability of liquid crystalline phases for the rod–coil bilayers. Abstract : The structure and phase behaviour of bilayer membranes self-assembled from rod–coil diblock copolymers are studied using the self-consistent field theory, focusing on the occurrence and relative stability of liquid crystalline phases induced by the geometric shape and orientational interaction of the rod-blocks. A variety of liquid crystalline bilayers, corresponding to the smectic phases in bulk systems, are predicted to occur as equilibrium phases of the system. The ordered morphologies and phase behaviour of the system are analyzed. Phase diagrams of the self-assembled bilayers are constructed. The theoretical results provide an understanding of the formation mechanisms of these intricate phases.